Effects of modified ultrafiltration and conventional ultrafiltration combination on perioperative clinical outcomes in pediatric cardiac surgery: A meta-analysis. Issue 3 (22nd January 2021) - Hu, Jiajia; Li, Ping; Chen, Xuliang; Yan, Jianqin; Zhang, Junjie; Zhang, Chengliang
Abstract: Background: This meta-analysis was performed to review the effects of the addition of modified ultrafiltration (MUF) and conventional ultrafiltration (CUF) to CUF alone on postoperative hemoglobin, surgical and ultrafiltration data, and postoperative clinical outcomes in pediatric patients undergoing cardiac surgery. Methods: A systematic search was performed to identify randomized controlled clinical trials that compared MUF and CUF combination with CUF alone in pediatric cardiac surgery undergoing cardiopulmonary bypass (CPB) in PubMed, Embase, Cochrane Library, and Web of Science without any language or date limitation in February 2020. For each included trial, the primary outcomes including post-CPB and postoperative hematocrit, surgical and ultrafiltration data, postoperative clinical outcomes including volume of chest tube drainage within 48 hours after surgery and perioperative blood requirement, ventilation support duration, and length of stay day in the intensive care unit (ICU) and hospital were collected and analyzed. The analysis was conducted using STATA version 12.0. Results: A total of 8 trials encompassing 405 patients were included in this analysis. Analysis indicated that MUF + CUF increased the post-CPB hematocrit (Standard mean difference, SMD = 1.85, 95% confidence interval, 95% CI 0.91–2.79). Meanwhile, ultrafiltration volume was higher in CUF+MUF infants than CUF-alone infants (SMD = 1.46, 95% CI 0.51–2.41, P  = .003). The clinical outcomes, including postoperative hemodynamic changes, prime volume, blood requirement, chest tube drainage volume, mechanical ventilation duration, and ICU duration, were unclear because of the unstable sensitivity analyses. Conclusions: Beneficial effects of using MUF and CUF for pediatric cardiac surgery, including increase post-CPB hematocrit and ultrafiltration volume when compared with CUF alone. Meanwhile, MUF and CUF did not significantly influence the postoperative hospital stay duration, CPB, and aortic occlusion duration.